(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The study of tear fluid cytokines after keratorefractive surgery is important for assessing local inflammation and corneal regeneration after LASIK and Femto-LASIK. Objective. To perform clinical monitoring of tear fluid cytokine levels in patients after LASIK and Femto-LASIK. Materials and methods. This prospective study included 40 patients, 80 eyes, with mild to moderate myopia and myopic astigmatism. Two groups were formed, each including 20 patients and 40 eyes. LASIK was performed in the comparison group, while Femto-LASIK was performed in the main group. On postoperative day 3, tear fluid levels of IL-1β, IL-4, and TNF-α were determined. Results. After LASIK, the pro-inflammatory cytokines IL-1β and TNF-α were detected more often and at higher levels than after Femto-LASIK. In contrast, IL-4 was detected more often after Femto-LASIK and showed higher values. In the same group, pain relief occurred faster, epithelialization was completed earlier, and the RTSP parameter recovered sooner. The differences were statistically significant at p<0.05. Conclusion. After Femto-LASIK, the local immune response and regenerative process were more favorable than after LASIK, indicating lower tissue trauma with this technology.